2013
DOI: 10.1371/journal.pone.0065210
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fat Content, Evaluated through Semi-Quantitative Ultrasound Measurement, Is Associated with Impaired Glucose Profiles: A Community-Based Study in Chinese

Abstract: Nonalcoholic fatty liver disease (NAFLD) is closely associated with type 2 diabetes mellitus. We investigated whether the deposition of fat in the liver is associated with glycemic abnormalities and evaluated the contribution of the liver fat content (LFC) to the impaired glucose regulation. We conducted a community-based study among 2836 residents (1018 males and 1818 females) without prior known diabetes mellitus from the Changfeng Study who were at least 45 years old. A standard interview, anthropometrics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…The liver fat content determined by the quantitative ultrasound method showed an excellent correlation and consistency with that obtained by proton magnetic resonance ( r = 0.89, P < 0.001), and a good correlation with the histology‐determined steatosis grade ( r = 0.79, P < 0.001) . It has previously been evaluated and used for large‐scale population studies …”
Section: Methodsmentioning
confidence: 65%
See 2 more Smart Citations
“…The liver fat content determined by the quantitative ultrasound method showed an excellent correlation and consistency with that obtained by proton magnetic resonance ( r = 0.89, P < 0.001), and a good correlation with the histology‐determined steatosis grade ( r = 0.79, P < 0.001) . It has previously been evaluated and used for large‐scale population studies …”
Section: Methodsmentioning
confidence: 65%
“…In our previous study, we established a method for the computer‐aided ultrasound measurement of LFC based on the ultrasound hepatic/renal ratio and hepatic attenuation rate using a traditional ultrasonic apparatus, and the accuracy of the quantitative ultrasound examination was established using [ 1 H]‐MRS as a reference and was consistent with both [ 1 H]‐MRS ( r = 0.89, P < 0.001) and the histology‐determined steatosis grade ( r = 0.79, P < 0.001) . The method has also previously been evaluated and used for large‐scale population studies . Therefore, we can quantitatively analyse the associations of the liver fat content by quantitative ultrasonography and metabolic parameters.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this study, the hepatic/renal ratio and hepatic echo-intensity attenuation rate were highly correlated with 1 H-MRS liver fat content; suggesting that these methods could also accurately assess liver fatty content as well. Compared with 1 H-MRS, these methods are more convenient, economic, and easy to operate [3,12,13] , which can be used as new tools for clinical NAFLD diagnosis.…”
Section: H-mrs Liver Fat Contentmentioning
confidence: 99%
“…NAFLD was also reported to be associated with increased insulin resistance [2] . A meta-analysis showed that the prevalence of diabetes significantly increased in patients with NAFLD, and was 2-3 times higher than normal [3] . If the disease is not diagnosed early, abnormal glucose metabolism and cardiovascular disease could easily manifest in patients with NAFLD.…”
Section: Introductionmentioning
confidence: 99%